The role of DNA methylation and demethylation in bladder cancer: a focus on therapeutic strategies - Strasenburg, Wiktoria; Borowczak, Jędrzej; Piątkowska, Daria; Jóźwicki, Jakub; Grzanka, Dariusz (Frontiers in Oncology, 2025)
DNA methylation is the best-known epigenetic mechanism regulating gene expression without altering the DNA sequence. Its counterpart, known as DNA demethylation, is equally important and enables the activation of previously silenced genes. DNA demethylation has attracted interest in the scientific community following the landmark discovery that Ten-Eleven Translocation (TET) proteins can convert 5-methylcytosine to 5-hydroxymethylcytosine. A growing body of research indicates that changes in TET protein levels and 5-hydroxymethylcytosine content are hallmarks of cancer. These epigenetic changes appear to play a critical role in the development of malignancies characterized by high levels of somatic mutations and genetic instability. Bladder cancer is among the most common cancers worldwide and, despite aggressive treatment, remains associated with high mortality and poor prognosis. The lack of reliable diagnostic and prognostic markers poses a significant challenge in its management, highlighting the urgent need for novel biomarkers to enable earlier diagnosis and more accurate prediction of clinical outcomes. This review examines epigenetic alterations associated with bladder cancer and their clinical implications. We focus on the impact of DNA methylation and demethylation on oncogene regulation, summarize scientific evidence supporting their role in bladder cancer development and progression, and briefly explore novel therapeutic strategies targeting those epigenetic mechanisms.